2017
DOI: 10.5423/ppj.nt.06.2016.0144
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Explain Temperature Dependent Systemic Infection of Potato Plants by Potato virus Y

Abstract: The effect of temperature on the rate of systemic infection of potatoes (Solanum tuberosum L. cv. Chu-Baek) by Potato virus Y (PVY) was studied in growth chambers. Systemic infection of PVY was observed only within the temperature range of 16°C to 32°C. Within this temperature range, the time required for a plant to become infected systemically decreased from 14 days at 20°C to 5.7 days at 28°C. The estimated lower thermal threshold was 15.6°C and the thermal constant was 65.6 degree days. A systemic infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In consequence, PepMV incidence can be underestimated and its unintended dispersion increase. High temperatures in growth chambers reduce three-fold the time necessary for PVY infection to become systemic in potato plants [146]. In the case of tobamovirus resistance in pepper, it has been reported and commonly observed in the field that L alleles lose efficiency above 30 • C [147].…”
Section: Effects Of Climate Change On Viruses and Vectorsmentioning
confidence: 99%
“…In consequence, PepMV incidence can be underestimated and its unintended dispersion increase. High temperatures in growth chambers reduce three-fold the time necessary for PVY infection to become systemic in potato plants [146]. In the case of tobamovirus resistance in pepper, it has been reported and commonly observed in the field that L alleles lose efficiency above 30 • C [147].…”
Section: Effects Of Climate Change On Viruses and Vectorsmentioning
confidence: 99%
“…cabbage when temperature was increased from 13 to 23-28 • C (Chung et al, 2015) and a GFP-tagged version of this virus shows a twofold more efficient cell-to-cell (Figures 2A,B) and systemic (Figures 2C,D) spread in canola (Brassica napus) upon shifting the daytime temperature by only four degrees from 24 to 28 • C. In Arabidopsis, TuMV was shown to accumulate to higher levels when kept at 25 • C during the day and 15 • C in the night as compared to colder temperatures with 15 • C during the day and 5 • C in the night (Honjo et al, 2020). Potato plants infected with Potato virus Y showed a dramatic increase in systemic infection when temperatures were increased from 23 to 28 • C (Choi et al, 2017). Barley yellow dwarf virus (BYDV) showed strong increases in systemic movement in oat when the temperature was elevated from 15.5 to 21 • C (Jensen, 1973) and infection of bean leaves with Rothamsted tobacco necrosis virus (RTNV) increased with rising temperature from 10 to 22 • C (Harrison, 1956).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, TuMV was shown to accumulate to higher levels when kept at 25°C during the day and 15°C in the night as compared to colder temperatures with 15°C during the day and 5°C in the night ( Honjo et al, 2020 ). Potato plants infected with Potato virus Y showed a dramatic increase in systemic infection when temperatures were increased from 23 to 28°C ( Choi et al, 2017 ). Barley yellow dwarf virus (BYDV) showed strong increases in systemic movement in oat when the temperature was elevated from 15.5 to 21°C ( Jensen, 1973 ) and infection of bean leaves with Rothamsted tobacco necrosis virus (RTNV) increased with rising temperature from 10 to 22°C ( Harrison, 1956 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the resistance phenotype can be modified, meaning that local necrotic lesions such as hypersensitive reaction (HR, a form of programmed cell death [25]) can be transformed into systemic necrosis. Additionally, extreme resistance, which inhibits virus replication without apparent HR, can be shifted to HR or even to systemic necrosis at temperatures above 28-30 • C. In the absence of R genes, elevated temperature was shown to promote symptom severity, systemic spreading, and replication potential of viruses [26][27][28]. Other studies reported contradictory results in the sense that elevated temperatures reduced viral symptoms and viral accumulation [29][30][31], which was hypothesized to be attributable to increased efficiency of the RNA silencing pathway at elevated temperature [32].…”
Section: Introductionmentioning
confidence: 99%